ANALYSING THE LEVEL OF ORGANIC CHEMISTRY ANXIETY OF PRE-SERVICE EDUCATION STUDENTS - Munasprianto Ramli (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
ANALISIS TINGKAT KECEMASAN KIMIA ORGANIK MAHASISWA PRA JASA PENDIDIKANAbstractSeveral studies have reported that poor performance of organic chemistry among students has been attributed partly to organic chemistry anxiety. The purpose of this study is to investigate the level of organic chemistry anxiety among chemistry education students. Sequential explanatory mixed methods approach employed in the study. Due to COVID-19 Pandemic, 142 pre-service education students from four universities were chosen using the convenience sampling technique. The questionnaires were distributed to the participants using google form. This quantitative data generation was followed by a semi-structured interview with 2 students from each university. Quantitative data gathered were analyzed using descriptive statistics meanwhile qualitative data from interviews were analyzed using thematic analysis. The results show that 5.63% of students have low anxiety, 81.69% of students have moderate anxiety levels, while 12.68% of students have high anxiety levels. On average the anxiety level of chemistry education students is at a moderate level with a score was 62. According to students, this anxiety was influenced by the complexity of organic chemistry lesson materials, lecturer strategies in teaching organic chemistry, and their previous knowledge of chemistry. Further study should be carried out to analyze the factors that influence students’ anxiety.AbstrakSejumlah penelitian telah melaporkan bahwa buruknya performa mahasiswa pada mata kuliah kimia organik berkaitan dengan kecemasan mereka terhadap kimia organik. Tujuan dari penelitian ini adalah untuk mengetahui tingkat kecemasan mahasiwa Pendidikan Kimia terhadap perkuliahan Kimia Organik. Pendekatan metode campuran eksplanatori sekuensial digunakan dalam penelitian ini. Akibat Pandemi COVID-19, sebanyak 142 mahasiswa Pendidikan kimia dari empat universitas dengan menggunakan teknik convenience sampling. Kuisioner dibagikan kepada peserta menggunakan google form. Penyebaran kuesioner ini dilanjutkan dengan wawancara semi struktur dengan 2 mahasiswa dari masing-masing universitas. Data kuantitatif yang terkumpul dianalisis menggunakan statistik deskriptif sedangkan data kualitatif dari wawancara dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan 5,63% siswa memiliki tingkat kecemasan rendah, 81,69% siswa memiliki tingkat kecemasan sedang, sedangkan 12,68% siswa memiliki tingkat kecemasan tinggi. Rata-rata tingkat kecemasan mahasiswa pendidikan kimia berada pada tingkat sedang dengan skor 62. Menurut mahasiswa, kecemasan ini dipengaruhi oleh kompleksitas materi pelajaran kimia organik, strategi dosen dalam pembelajaran kimia organik dan pengetahuan sebelumnya tentang kimia. Studi lebih dapat dilakukan untuk menganalisis faktor-faktor yang mempengaruhi kecemasan siswa.